Changes in soil pH and crop growth following the application of lime-amended biosolids - Pritchard, Deborah; Collins, David; Allen, D.; Penney, N. (Aqua Enviro Technology Transfer, 2007)
Approximately half of all the agricultural soils in Australia are affected by soil acidity. Ground limestone is a product used by farmers to better manage and neutralise soil acidity and to improve plant productivity. The effect of lime-amended biosolids (LAB) as an alternative product for neutralising soil acidity was applied at four rates (0, 5, 10 and 15 t DS/ha) and compared with equivalent rates of lime (0, 2.3, 4.6 and 6.7 t/ha) and one rate of dewatered biosolids cake (DBC) (7 t DS/ha) in a wheat/canola cropping rotation on an acidic red/brown sandy loam in the wheatbelt of Western Australia. Soil pH (CaCl2) in the surface soil (0-10 cm) increased significantly with increasing rates of either LAB or lime at the end of the first year, increasing from 4.4 to 7.2, with similar values recorded between equivalent values of lime product. The DBC treatment did not change soil pH. No further changes in soil pH had occurred by the end of the second year. The increased yield of wheat with increasing rates of LAB in the first season was attributed to improved nutrition rather than to the overall reduction in soil acidity. The experiment is ongoing and has been sown to wheat in 2007 to further monitor the effects of LAB over time.